2015
DOI: 10.2967/jnumed.115.161661
|View full text |Cite
|
Sign up to set email alerts
|

Promising New 18F-Labeled Tracers for PET Myocardial Perfusion Imaging

Abstract: Myocar dial perfusion imaging with PET offers several advantages over SPECT for the detection and characterization of coronary artery disease. With PET, individual tissue-density measurements are routinely used to correct the emission images for photon attenuation and scatter by interposed tissue. And because PET scanners have higher spatial resolutions and count sensitivities than SPECT scanners, PET images can discriminate more readily between areas with normal and abnormal perfusion. As a result, PET imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Lower HU densities in these segments have previously been documented in MPI studies (Burrell & MacDonald, 2006;Dvorak et al, 2011;Brunken, 2015). The lowest values were detected in the inferoseptal segments.…”
Section: Figuresupporting
confidence: 64%
See 1 more Smart Citation
“…Lower HU densities in these segments have previously been documented in MPI studies (Burrell & MacDonald, 2006;Dvorak et al, 2011;Brunken, 2015). The lowest values were detected in the inferoseptal segments.…”
Section: Figuresupporting
confidence: 64%
“…The lowest values were detected in the inferoseptal segments. Lower HU densities in these segments have previously been documented in MPI studies (Burrell & MacDonald, 2006;Dvorak et al, 2011;Brunken, 2015). Studies investigating the diagnostic accuracy of TPR have reported a threshold <0.99 to be sensitive for detection of myocardial ischaemia due to haemodynamically significant stenosis (George et al, 2009;Ko et al, 2012).…”
Section: Figurementioning
confidence: 77%
“…1; Suppl. Figure 1) [1315]. It was also shown that 18 F-FPTP has greater first-pass myocardial extraction than 13 N-ammonia in isolated perfused rat heart, indicating the suitability of 18 F-FPTP as a quantitative myocardial PET imaging agent [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1) [1315]. It was also shown that 18 F-FPTP has greater first-pass myocardial extraction than 13 N-ammonia in isolated perfused rat heart, indicating the suitability of 18 F-FPTP as a quantitative myocardial PET imaging agent [14, 15]. In addition, no metabolite was detected in the serum of mice 30 min after intravenous injection of 18 F-FPTP, implying that the metabolite correction would not be necessary in the kinetic analysis of 18 F-FPTP myocardial PET data [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation